Applied theatre: International Case Studies and Challenges for Practice - Prendergast, Monica; Saxton, Juliana (Intellect, 2016)
Theatre practice and applied theatre are areas of growing international interest. Applied Theatre is the first study to assist practitioners and students to develop critical frameworks for planning and implementing their own theatrical projects. This reader-friendly text considers an international range of case studies in applied theatre through discussion questions, practical activities and detailed analysis of specific theatre projects globally. In addition, the collection gathers together essential readings from many different sources to provide a comprehensive international survey of the fie.